Peran Mahasiswa KKN UMP dalam Mendorong Pembelajaran Kreatif di SD Negeri 4 Majakerta, Pemalang - Vina Rachmawati; Nur Rafif Sakti Pratama; Rizal Maryanto; Nabila Sasi Kirani; Dwi Astuti; Salsabila Anindya Putri; Catherine Putri Wulandari; Trisnadi Kholiq; Zahra Hafid Kirana (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
KKN (Real Work Lecture) activities are activities that every 7th semester student must participate in in KKN (Real Work Lecture) activities. Several students from the Muhammadiyah University of Purwokerto carried out KKN (Real Work Lecture) activities in Majakerta Village, Watukumpul District, Pemalang Regency in July – August 2024. The students who carried out KKN (Real Work Lecture) in Majakerta Village were 3 students and 6 female students. These students come from 7 faculties and 9 study programs. The way or method of implementing the activities is based on field surveys carried out by KKN participants during several visits to observe the conditions of the country where they live for a month. Then the KKN participants socialize with the local community to introduce themselves and provide information on the location of the participants with the aim of helping the local community and helping find solutions to existing problems. Several educational institutions in Majakerta Village are the destination for KKN student work programs. All KKN students play a role in implementing rural education through creative learning that is more interactive and innovative.